Photocatalytic discoloration of organic dyes in water dispersion medium by anatase-based binary nanocomposites - O. M. Lavrynenko; M. M. Zahornyi; O. Yu. Pavlenko; E. Paineau (Хімія, фізика та технологія поверхні, 2024)
Currently, textile and food industries produce a significant volume of sewages containing azo dyes and other organic pollutants. These effluents are serious environmental threats, so new methods for their treatment and the degradation of azo dyes are attracting much attention. Composite materials based on TiO2 modified by noble metals and nanoceria show high activity in the photodegradation of organic contaminates and are proposed for hydrogen synthesis as well. To optimize the treatment of contaminants, different processes can combine including the strategies of adsorption, photoluminescence, photocatalysis, etc. The synthesized TiO2-based nanomaterials (sols, powders) will be exploited for bioremediation due to their small size and surface plasmon resonance from noble metals. Binary nanocomposites based on TiO2 were obtained by the chemical co-precipitation method from solutions of titanium tetraisopropoxide (TTIP) and inorganic salts of cerium, silver, and palladium. It has been stated that TiO2 is represented by anatase with primary particle size (CSR) from 8.5 to 16.8 nm, depending on the nature and concentration of the dopant. It is shown that Ag is reduced on the surface of anatase particles and blocks their growth, while Pd and Ce penetrate the titanium dioxide matrix in the form of small clusters with the deformation of the anatase crystal lattice. Nanocomposite particles formed loose and fragile aggregates, which spontaneously dispersed in solutions of dyes with the formation of colloid-stable sols, required the use of a centrifugal field for their sedimentation. Nanoparticles of TiO2&Pd were electronegative and others were electropositive according to the values 4.1?9.6 of ZPC (zero point of charge). It was shown that the particles of all composites sorbed Methylene Blue (MB) without photocatalytic activity under the visible light to any dye. Moreover, anionic dyes such as Orange-G (Or-G) and Methyl Orange (MO) were excellently discolorated in the presence of TiO2&Pd system; cationic dyes of MB and Rhodamine B (RhB) discolorated too with the TiO2, TiO2&CeO2, and TiO2&Ag systems under UV light action. As such, photocatalysis tests showed that Orange-G’s and MO’s discoloration was higher for TiO2&Pd (2 wt. %) and TiO2 systems with the correlation coefficient R2 0.999.